2018
DOI: 10.3390/ijerph15081585
|View full text |Cite
|
Sign up to set email alerts
|

Household Food Insecurity and Mental Health Among Teenage Girls Living in Urban Slums in Varanasi, India: A Cross-Sectional Study

Abstract: This study was undertaken to investigate the relation between household food insecurity and mental health problems in teenage girls living in urban slums. This community-based cross-sectional study was conducted in 5 urban slums in Varanasi, India, between September 2016 and July 2017. A probability proportion to size (PPS) method was employed to select 5 of 210 urban slums at a first stage, and in the second stage, 418 teenage girls were chosen randomly from selected households. The Household Food Insecurity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 53 publications
0
28
1
Order By: Relevance
“…In turn, food insecurity is associated with elevated vulnerability to mental health challenges [25]. A study with adolescent girls living in slums in India reported associations between food insecurity and depression [26]. There is an urgent need to understand intervenable contextual factors that shape mental health with urban refugee and displaced youth living in slums to inform tailored programming.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, food insecurity is associated with elevated vulnerability to mental health challenges [25]. A study with adolescent girls living in slums in India reported associations between food insecurity and depression [26]. There is an urgent need to understand intervenable contextual factors that shape mental health with urban refugee and displaced youth living in slums to inform tailored programming.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to NCDs, mental health is an essential issue in this areas, especially in women and youth (35,36). A Cross-Sectional Study among teenage girls living in urban slums in India revealed more than half of them had high levels of anxiety, depression, or psychological distress (59). These situations could be modi ed through participatory community-based interventions (60).…”
Section: Discussionmentioning
confidence: 99%
“…Details of the study settings, participants, and other methodological details are described elsewhere. 28…”
Section: Study Design Setting and Participantsmentioning
confidence: 99%
“…The details of food insecurity and mental health status measurement is available from our previous publication. 28…”
Section: Household Food Security and Mental Health Statusmentioning
confidence: 99%
See 1 more Smart Citation